Analysis of the Implementation of the Hypertension Control Program Using Linear Regression Test - Liss Dyah Dewi Arini; Linda Widyaningrum; Darah Ifalahma; Yeni Nurmalitasari; Azahra Salma Salsabila Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension is a condition that is often encountered. Hypertension is a condition when blood pressure rises. Risk factors that can cause hypertension are age, race, gender, lifestyle, sodium consumption, smoking, alcohol consumption, stress level, and education. The urgency of this research is that the number of hypertension patients at the Purwodiningratan Surakarta Health Center experiences a spike every year. Based on a preliminary study at the Community Health Center, data was obtained that the number of hypertension patients in the last five year period experienced a spike, then fell, then spiked again. The objective problem of this research is the increase in hypertension patients, so it is necessary to research the relationship between knowledge, attitudes and family support and efforts to control hypertension. The importance of this research is a manifestation of efforts to control hypertension which continues to experience a surge using interview methods and distributing leaflets with the aim of a community approach. The aim of the research is to analyze the magnitude of the impact of the hypertension control program using the swallow method (interviews and leaflets). The research approach used cross sectional. The sample was 77 hypertensive patients at the Community Health Center. The sampling technique used the accidental sampling method based on inclusion and exclusion criteria. The statistical test uses a linear regression test at a significance level of 0.05.